Bi-reforming of model biogas to syngas over Ru nano-catalysts supported on Mg-Al oxide derived from layered double hydroxides. (1st July 2023) - Zhong, Jiawei; Han, Bing; Zhang, Zhige; Bi, Guican; Xie, Jun
Graphical abstract: Highlights: The basic Mgx (Al)O facilitate the CO2 activation and generation of O* species, contributed to prompt removal of coke precursor and effective coke-resistance behavior. The highly-dispersed Ru ultrafine NPs inhibit coke deposition due to size effect, the interaction between Ru NPs and Mgx (Al)O result in satisfying anti-sintering performance. Ru/Mgx (Al)O (x=4, 5) show excellent catalytic performance in bi-reforming of model biogas. Abstract: A series of Ru/Mgx (Al)O (x=3, 4, 5) nano-catalysts, derived from Ru/MgAl layered double hydroxide, were facilely synthesized. The properties of Ru/Mgx (Al)O catalysts, before and after stability tests, were comprehensively characterized via N2 physisorption, XRD, ICP-OES, XRF, SEM, H2- TPR, CO2 -TPD, XPS, TEM, TGA, Raman spectroscopy. In the bi-reforming of model biogas, at 800 °C, CH4 /CO2 /N2 /H2 O = 3/2/1/2.6, WHSV = 30960 mL g −1 h −1, 0.7Ru/Mg4 (Al)O and 0.9Ru/Mg5 (Al)O catalysts display high catalytic activity and stability without obvious deactivation within 100 h time-on-stream. The basic Mgx (Al)O mixed oxides facilitate the CO2 activation and generation of active O* species, contributed to prompt removal of coke precursor and effective coke-resistance behavior. The highly-dispersed Ru ultrafine NPs also contributed to the inhibited coke deposition due to size effect. In addition, the strong interaction between Ru NPs and Mgx (Al)O mixed oxides, result in the satisfying anti-sintering performance. The combined support effect, size effect as well as metal-support interaction over Ru/Mgx (Al)O (x=4, 5) catalyst result in excellent catalytic performance.